At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Let’s verify the given trigonometric identity step by step:
[tex]\[ \frac{1 - \sin^4 A}{\cos^4 A} = 1 + 2 \tan^2 A \][/tex]
### Step 1: Simplify the Left-Hand Side
We start with:
[tex]\[ \frac{1 - \sin^4 A}{\cos^4 A} \][/tex]
Using the identity [tex]\( \sin^2 A + \cos^2 A = 1 \)[/tex], we know that [tex]\( \sin^2 A = 1 - \cos^2 A \)[/tex]. Consequently, we can express [tex]\( \sin^4 A \)[/tex] as:
[tex]\[ \sin^4 A = (\sin^2 A)^2 = (1 - \cos^2 A)^2 \][/tex]
Therefore, the expression becomes:
[tex]\[ \frac{1 - \sin^4 A}{\cos^4 A} = \frac{1 - (1 - \cos^2 A)^2}{\cos^4 A} \][/tex]
### Step 2: Expand and Simplify the Numerator
Expand [tex]\( (1 - \cos^2 A)^2 \)[/tex]:
[tex]\[ (1 - \cos^2 A)^2 = 1 - 2\cos^2 A + \cos^4 A \][/tex]
Substitute back into the numerator:
[tex]\[ 1 - (1 - 2\cos^2 A + \cos^4 A) = 1 - 1 + 2\cos^2 A - \cos^4 A \][/tex]
[tex]\[ = 2\cos^2 A - \cos^4 A \][/tex]
Therefore, the expression now is:
[tex]\[ \frac{2\cos^2 A - \cos^4 A}{\cos^4 A} \][/tex]
### Step 3: Simplify the Fraction
Separate the terms in the numerator:
[tex]\[ \frac{2\cos^2 A - \cos^4 A}{\cos^4 A} = \frac{2\cos^2 A}{\cos^4 A} - \frac{\cos^4 A}{\cos^4 A} \][/tex]
[tex]\[ = \frac{2}{\cos^2 A} - 1 \][/tex]
Recognizing that:
[tex]\[ \frac{1}{\cos^2 A} = \sec^2 A \][/tex]
[tex]\[ \frac{2}{\cos^2 A} = 2\sec^2 A \][/tex]
So the left-hand side simplifies to:
[tex]\[ 2\sec^2 A - 1 \][/tex]
### Step 4: Simplify the Right-Hand Side
We note that:
[tex]\[ \tan^2 A = \frac{\sin^2 A}{\cos^2 A} \][/tex]
So,
[tex]\[ 1 + 2\tan^2 A = 1 + 2 \frac{\sin^2 A}{\cos^2 A} \][/tex]
Using the Pythagorean identity, we know:
[tex]\[ \sec^2 A = 1 + \tan^2 A \][/tex]
Thus,
[tex]\[ \sec^2 A = \frac{1}{\cos^2 A} \][/tex]
Hence,
[tex]\[ 1 + 2\tan^2 A = 1 + 2(\frac{\sin^2 A}{\cos^2 A}) = 2\sec^2 A - 1 \][/tex]
### Conclusion
Both the left-hand side and right-hand side simplify to:
[tex]\[ 2\sec^2 A - 1 \][/tex]
Therefore, the given identity holds true:
[tex]\[ \frac{1 - \sin^4 A}{\cos^4 A} = 1 + 2\tan^2 A \][/tex]
[tex]\[ \frac{1 - \sin^4 A}{\cos^4 A} = 1 + 2 \tan^2 A \][/tex]
### Step 1: Simplify the Left-Hand Side
We start with:
[tex]\[ \frac{1 - \sin^4 A}{\cos^4 A} \][/tex]
Using the identity [tex]\( \sin^2 A + \cos^2 A = 1 \)[/tex], we know that [tex]\( \sin^2 A = 1 - \cos^2 A \)[/tex]. Consequently, we can express [tex]\( \sin^4 A \)[/tex] as:
[tex]\[ \sin^4 A = (\sin^2 A)^2 = (1 - \cos^2 A)^2 \][/tex]
Therefore, the expression becomes:
[tex]\[ \frac{1 - \sin^4 A}{\cos^4 A} = \frac{1 - (1 - \cos^2 A)^2}{\cos^4 A} \][/tex]
### Step 2: Expand and Simplify the Numerator
Expand [tex]\( (1 - \cos^2 A)^2 \)[/tex]:
[tex]\[ (1 - \cos^2 A)^2 = 1 - 2\cos^2 A + \cos^4 A \][/tex]
Substitute back into the numerator:
[tex]\[ 1 - (1 - 2\cos^2 A + \cos^4 A) = 1 - 1 + 2\cos^2 A - \cos^4 A \][/tex]
[tex]\[ = 2\cos^2 A - \cos^4 A \][/tex]
Therefore, the expression now is:
[tex]\[ \frac{2\cos^2 A - \cos^4 A}{\cos^4 A} \][/tex]
### Step 3: Simplify the Fraction
Separate the terms in the numerator:
[tex]\[ \frac{2\cos^2 A - \cos^4 A}{\cos^4 A} = \frac{2\cos^2 A}{\cos^4 A} - \frac{\cos^4 A}{\cos^4 A} \][/tex]
[tex]\[ = \frac{2}{\cos^2 A} - 1 \][/tex]
Recognizing that:
[tex]\[ \frac{1}{\cos^2 A} = \sec^2 A \][/tex]
[tex]\[ \frac{2}{\cos^2 A} = 2\sec^2 A \][/tex]
So the left-hand side simplifies to:
[tex]\[ 2\sec^2 A - 1 \][/tex]
### Step 4: Simplify the Right-Hand Side
We note that:
[tex]\[ \tan^2 A = \frac{\sin^2 A}{\cos^2 A} \][/tex]
So,
[tex]\[ 1 + 2\tan^2 A = 1 + 2 \frac{\sin^2 A}{\cos^2 A} \][/tex]
Using the Pythagorean identity, we know:
[tex]\[ \sec^2 A = 1 + \tan^2 A \][/tex]
Thus,
[tex]\[ \sec^2 A = \frac{1}{\cos^2 A} \][/tex]
Hence,
[tex]\[ 1 + 2\tan^2 A = 1 + 2(\frac{\sin^2 A}{\cos^2 A}) = 2\sec^2 A - 1 \][/tex]
### Conclusion
Both the left-hand side and right-hand side simplify to:
[tex]\[ 2\sec^2 A - 1 \][/tex]
Therefore, the given identity holds true:
[tex]\[ \frac{1 - \sin^4 A}{\cos^4 A} = 1 + 2\tan^2 A \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.